Acute responses of soccer match play on hip strength and flexibility measures: potential measure of injury risk - Paul, D. J.; Nassis, G. P.; Whiteley, R.; Marques, J. B.; Kenneally, D.; Chalabi, H. (Journal of Sports Sciences, 2014)
Regular measurements of groin risk factors may offer a preventive measure against injury. Therefore, the aim of this study was to (1) determine minimal detectable change (MDC) and reliability of hip flexibility and strength measures and to (2) identify the effect soccer match play load has on these measures. Reliability was determined for bent knee fall out test, hip abduction and adduction (hand-held dynamometry (HHD)) in 20 trained youth male soccer players. Reliability was evaluated with the intra-class correlation coefficient (ICC[2,1]), 95% confidence intervals (CI). Hip strength and flexibility measures were taken before and after an international friendly match. Intra-rater reliability ICC ranges were bent knee fall out (0.75-0.90), abduction (0.83-0.90) and adduction (0.72-0.96). Inter-rater ICCs (95% CI) were bent knee fall out test [0.75 (0.39-0.90) right, 0.71 (0.27-0.89) left hip]; abduction [0.80 (0.50-0.92) right, 0.81 (0.53-0.92) left hip] and adduction [0.72 (0.31-0.89) right, 0.70 (0.26-0.88) left hip]. MDCs were as low as 20.7% of the mean for hip flexibility and 12.5% for strength. In conclusion, HHD and the bent knee fall out test are reliable tools to measure changes in hip strength and flexibility. Finally, a threshold may exist in which match play load negatively impacts hip flexibility.